House dust mites as potential carriers for IgE sensitization to bacterial antigens. Issue 1 (7th September 2017) - Dzoro, S.; Mittermann, I.; Resch‐Marat, Y.; Vrtala, S.; Nehr, M.; Hirschl, A. M.; Wikberg, G.; Lundeberg, L.; Johansson, C.; Scheynius, A.; Valenta, R.
Abstract: Background: IgE reactivity to antigens from Gram‐positive and Gram‐negative bacteria is common in patients suffering from respiratory and skin manifestations of allergy, but the routes and mechanisms of sensitization are not fully understood. The analysis of the genome, transcriptome and microbiome of house dust mites (HDM) has shown that Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ) species are abundant bacteria within the HDM microbiome. Therefore, our aim was to investigate whether HDM are carriers of bacterial antigens leading to IgE sensitization in patients suffering from atopic dermatitis. Methods: Plasma samples from patients with AD (n = 179) were analysed for IgE reactivity to a comprehensive panel of microarrayed HDM allergen molecules and to S. aureus and E. coli by IgE immunoblotting. Antibodies specific for S. aureus and E. coli antigens were tested for reactivity to nitrocellulose‐blotted extract from purified HDM bodies, and the IgE‐reactive antigens were detected by IgE immunoblot inhibition experiments. IgE antibodies directed to bacterial antigens in HDM were quantified by IgE ImmunoCAP™ inhibition experiments. Results: IgE reactivity to bacterial antigens was significantly more frequent in patients with AD sensitized to HDM than in AD patients without HDM sensitization. S. aureus and E. coli antigens were detected in immune‐blotted HDM extract, and the presence of IgE‐reactive antigens in HDM was demonstrated by qualitative and quantitative IgE inhibition experiments. Conclusion: House dust mites (HDM) may serve as carriers of bacteria responsible for the induction of IgE sensitization to microbial antigens.